KAIZEN AS A SYSTEM FOR STRATEGIC COST MANAGEMENT IN THE REALIZATION OF COMPETITIVE ADVANTAGES - Jolović, Ivana; Petković, Đerđi (Ekonomija - teorija i praksa, 2022)
Managing a company in contemporary, dynamic business conditions must be strategically oriented. The competition forces companies to constantly reduce all types of costs incurred in preproduction and production processes, with the obligation to maintain the quality of manufactured products at a satisfactory level. Such requirements can be achieved only by adequate strategic planning of all production processes, and by strategic management of costs. In this context, Kaizen as a cost management system can be characterized as an ideal strategic tool and a source of competitiveness, since by its application organization can plan its production activities in detail, organize them in a way that fully complies with the principles of efficiency and effectiveness, and minimize waste and unwanted losses of available resources. The aim of the research is to consider the Kaizen concept as a system for managing (reducing) costs, and as a source of competitive advantage of a particular organization. The descriptive and comparative method, the technique of analysis and synthesis, as well as analysis of the content of relevant literature of reference domestic and foreign authors, were used for the research purposes. The result of the research is the confirmed assumption that the implementation of the Kaizen system in the company provides an atmosphere of constant improvement that leads to the reduction of production costs and increased market competitiveness.